Unintegrated human immunodeficiency virus type 1 DNA in chronically infected cell lines is not correlated with surface CD4 expression. - Besansky, N J (1991)
Using a polymerase chain reaction-based assay on total cell lysates, we have detected unintegrated human immunodeficiency virus type 1 (HIV-1) DNA in chronically infected T-lymphocytic (ACH-2, J1) and promyelocytic (OM-10.1) cell lines. Treatment with 3'-azido-3'-deoxythymidine (AZT) or soluble CD4 inhibited accumulation of unintegrated viral DNA about 10-fold within 72 h; removal of AZT permitted recovery to pretreatment levels within 72 h. Our results indicate that unintegrated HIV-1 DNA is unstable in these cell lines and originates from a continuous process of reinfection. OM-10.1 cells had relatively high levels of surface CD4 by flow cytometry and high levels of unintegrated viral DNA by polymerase chain reaction. ACH-2 cells had very low levels of both surface CD4 and unintegrated viral DNA. However, J1 cells, with surface CD4 below the level of detection of flow cytometry had a high level of unintegrated viral DNA similar to that of OM-10.1 cells. This implies that the number of CD4 receptors is not rate limiting for reinfection.